Influence of sustainability on regulation and credit risk management among commercial banks in Kenya - Lilian K. Nyamongo (Kenya Bankers Association (KBA), 2019)
This paper assesses the influence of sustainability on regulation and credit risk management among commercial banks in Kenya. Drawing from the concepts of risk and sustainable banking and the market signaling theory, primary data through questionnaires was collected supplemented by secondary data available from the banks' annual and sustainability reports on their respective sites. The study has shown that commercial banks in Kenya have embraced different attitudes and are at different stages in embedding sustainability in the credit risk management systems. The study has also confirmed that most banks are taking the precautionary approach in their credit risk assessment process by ensuring they meet the minimum legal requirements. It has become quite clear that they are meeting the required reporting requirements by the regulator but very few have embedded sustainability reporting as part of their standard financial reporting.
Keywords: 330; Green Credit; Sustainability; Kenya